BRET- and fluorescence anisotropy-based assays for real-time monitoring of ligand binding to M-2 muscarinic acetylcholine receptors - Gratz, Lukas; Laasfeld, Tonis; Allikalt, Anni; Gruber, Corinna G.; Pegoli, Andrea; Tahk, Maris-Johanna; Tsernant, Mari-Liis; Keller, Max; Rinken, Ago (Biochimica Et Biophysica Acta-Molecular Cell Research, 2021)
BRET and fluorescence anisotropy (FA) are two fluorescence-based techniques used for the characterization of ligand binding to G protein-coupled receptors (GPCRs) and both allow monitoring of ligand binding in real time. In this study, we present the first direct comparison of BRET-based and FA-based binding assays using the human M-2 muscarinic acetylcholine receptor (M2R) and two TAMRA (5-carboxytetramethylrhodamine)-labeled fluorescent ligands as a model system. The determined fluorescent ligand affinities from both assays were in good agreement with results obtained from radioligand competition binding experiments. The assays yielded real-time kinetic binding data revealing differences in the mechanism of binding for the investigated fluorescent probes. Furthermore, the investigation of various unlabeled M2R ligands yielded pharmacological profiles in accordance with earlier reported data. Taken together, this study showed that BRET- and FA-based binding assays represent valuable alternatives to radioactivity-based methods for screening purposes and for a precise characterization of binding kinetics supporting the exploration of binding mechanisms.
CRIS-Team WoS Importer:2021-02-12